(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
The purpose of the research was the study of the effect of dosed vibration training (DVT) on the dynamics of psy- chophysiological qualities of athletes. The objectives of the research consisted of the determination of the effects of the vibration load on the dynamics of the development of the psychomotor (high-speed, coordination) qualities of athletes. In this study 10 male athletes took part. The average age of the group of test subjects was 13.90 ± 0.18 years old, the average body mass 55.61 ± 3.12 kg, the average body height 171.50 ± 7.91 cm, the average muscle tissue mass 38.90 ± 2.85%, the average fat tissue mass 16.40 ± 2.17%, the average period of participation in sports 4.25 ± 0.5 years. Over the course of two training microcycles (14 days) in the period of general training of the yearly training macrocycle athletes performed the program of DVT, which consisted of 8 stimulation training sessions, with 4 training sessions in each of the two weekly microcycles. The vibration load was created by means of the perfor- mance of repeated physical exercises with the extremities resting on the vibration devices (platforms), working at the frequency of 28 Hz and amplitude of 4 mm. With the goal of creating conditions for the global effect of vibrations on the body integrated exercise was proposed to the test subjects covering the greatest mass of working muscles with the vibration effect. The exercise consisted of two parts, performed without a break: arm-pumping exercises from the initial position “sitting back with arms resting on the vibration platforms” and squats on the vibrating platforms. Each parts of the exercise was performed by every trainee until fatigue. In accordance with the program the vibra- tion load increased from training to training due to the addition of one set to the number of sets performed in each preceding series of exercises. In the ﬁ rst exercise the average time of the vibration load was 172 ± 12 seconds with an average total number of motion cycles of 169 ± 10, and in the last exercise 908±30 seconds with an average total number of motion cycles of 698 ± 31. On the basis of the results of the research it can be concluded that vibration training consisting of 8 stimulation series, equally distributed over the course of two microcycles, renders a positive inﬂ uence on the psychophysiologi- cal qualities of athletes. Valid (р < 0.05) improvement in speed of complex motor response (12%) was observed immediately after the end of the training series. The precision of the complex choice reaction improved by 56% in comparison with the original value and maximum tempo of motions within one month improved by 10%. So dozed vibrating training inﬂ uences psychophysiological qualities effectively and can be recommended for the introduction in the training process of elite athletes. Keywords: Dozed vibrating training (DVT), dozed vibration exercises (DVE), psychophysiological qualities, training microcycle, psychomotor reaction.